The natural immune molecules urinary Tamm–Horsfall protein and pentraxin 3 as predictors for recurrent urinary tract infection severity: a single-center self-control study - Zongping Li; Yingru Xu; Qian Wang; Gang Yuan; Jing Shu; Shiwei Liu; Xuezhong Gong (Renal Failure)
Objective The innate immune defense plays a pivotal role in protecting the urinary tract from uropathogenic invasion and maintaining immune homeostasis. Dysregulation of the innate immune system can result in recurrent urinary tract infections (RUTI) due to heightened susceptibility to uropathogens. Despite this, predicting the risk of recurrence and the degree of immune compromise in patients who have had one urinary tract infection remains challenging. Also identifying which patients are more susceptible to developing pyelonephritis rather than the more local disease of cystitis is imperfect, although delayed diagnosis of a UTI is a good indicator for developing pyelonephritis. This study aims to assess the potential of urinary Tamm-Horsfall protein (THP) and Pentraxin 3 (PTX3) as predictors of RUTI symptom severity and recurrence, while also evaluating the efficacy of the Chinese herbal formulation Tailin Formula (TLF) as a clinical therapeutic intervention for RUTI.Methods A single-center cohort study was conducted involving 142 participants, consisting of 31 healthy individuals (non-RUTI group, n = 31) and 111 patients with RUTI. The RUTI patients were divided into two groups: one group received continuous low-dose antibiotic therapy (CLAT group, n = 55), and the other group received herbal preparations (Tailin formula) (TLF group, n = 56). All patients received consistent lifestyle guidance. Descriptive analysis was performed on the RUTI cohort.Results Urinary THP levels were significantly lower in RUTI patients (TLF and CLAT groups) compared to the non-RUTI, whereas PTX3 levels showed a tendency toward elevation. After treatment, urinary THP levels were markedly higher in the TLF group (27.43 ± 7.07) compared to pretreatment levels (10.00 ± 2.79), while levels remained lower in the CLAT group (8.91 ± 2.23) than in the TLF group. Urinary PTX3 levels decreased post-treatment in both groups after treatment than before (CLAT: 0.30 ± 0.13 vs. 1.04 ± 0.38; TLF: 0.29 ± 0.12 vs. 1.15 ± 0.36). Additionally, THP was negatively correlated with renal tubular injury markers NAG/Cr and β2-MG in RUTI patients (r = −0.5041 and −0.6169, respectively), while PTX3 showed a positive correlation with NAG/Cr and β2-MG (r = 0.28 and 0.498, respectively). Notably, as RUTI symptoms improved and recurrence rates decreased, urinary THP levels increased, while PTX3 levels decreased.Conclusion This study suggests that urinary THP and PTX3 are likely involved in the pathogenesis of RUTI. These biomarkers may serve as valuable predictors for assessing symptom severity, recurrence risk, and therapeutic efficacy in patients with RUTI at risk of disease progression.